Հայ-վրացական պատերազմը «Ճակատամարտ» օրաթերթի էջերում - Հովսեփյան, Մարիամ (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
На страницах газеты «Чакатамарт» публиковались материалы, посвященные Армяно-грузинской войне, которые носили не только информативный, но и аналитический характер. При этом газета придерживалась принципов политкорректности, представляя объективную картину событий. The daily newspaper “ Chakatamart” covered the ongoing war between Armenia and Georgia. The articles not only introduced information on the war, but also included analyses of its underlying causes. Moreover, the newspaper prioritized political correctness and unbiased coverage of the war. The newspaper covered the conflict with utter neutrality and impartiality, highlighting the viewpoints of the parties involved.
Keywords: Պատմություն